2021
DOI: 10.1002/adma.202006832
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous High‐Temperature Superconductivity in YH6

Abstract: Pressure‐stabilized hydrides are a new rapidly growing class of high‐temperature superconductors, which is believed to be described within the conventional phonon‐mediated mechanism of coupling. Here, the synthesis of one of the best‐known high‐TC superconductors—yttrium hexahydride Im3¯m‐YH6 is reported, which displays a superconducting transition at ≈224 K at 166 GPa. The extrapolated upper critical magnetic field Bc2(0) of YH6 is surprisingly high: 116–158 T, which is 2–2.5 times larger than the calculated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
271
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 314 publications
(290 citation statements)
references
References 78 publications
14
271
2
3
Order By: Relevance
“…2a ) and the c / a ratios of bct- YH 4 and hcp -YH 9 (Fig. 2b ) agree well with the theoretical predictions 22 24 , 26 , 31 , 32 , which justifies the assignment of compositions for the hydrides with H/Y > 3.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…2a ) and the c / a ratios of bct- YH 4 and hcp -YH 9 (Fig. 2b ) agree well with the theoretical predictions 22 24 , 26 , 31 , 32 , which justifies the assignment of compositions for the hydrides with H/Y > 3.…”
Section: Resultssupporting
confidence: 85%
“…Here, we also discuss the contradictions between different experimental data for the yttrium-hydrogen system. Our preliminary report 25 and the present more comprehensive data are in good agreement with the data from Troyan et al 26 but evidently contradict the claim of T c = 262 K at 182 GPa reported by Snider et al 27 .…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…Other current participants in the race are hydrogen-rich materials, such as H 3 S, LaH 10 , Li 2 MgH 16 , YH 6 , etc. [81][82][83][84][85]. In these systems, the large transition temperature results from the large vibrations of light hydrogens, which increase the electron-phonon coupling.…”
Section: Discussionmentioning
confidence: 99%